IDENTITAS AGAMA DAN TOLERANSI DALAM INTERAKSI SOSIAL (STUDI KASUS DALAM MENYUARAKAN PEMBANGUNAN RUMAH IBADAH DI GARUT) - Bening Shabilla Utami; Turnomo Rahardjo; Wiwid Noor Rakhmad (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2022)
Religious sentiment often occurs in several areas in Indonesia, and continues to increase, where there are still many cases of religious intolerance. One of the cases was the refusal to build a house of worship for Christians in Dayeuhmanggung village. Christianity as a religion with smaller adherents in Dayeuhmanggung village coexists with Islam with larger adherents. The identity of each religion in which tolerance is established does not always work well due to lack of knowledge and lack of understanding of each other's culture. This study aims to find out how the interaction of the Muslim and Christian religious communities in personal and social activities in the village of Daya Manggung, Cilawu District, Garut Regency. The theory used is the theory of co-culture and the theory of cultural identity. This research is a descriptive study with a case study approach to look at the case in depth and examine the experiences of informants related to a phenomenon experienced with the main focus of communication interaction. In this study, using an in-depth interview technique to 3 adherents of Islam and 3 adherents of Christianity. The findings of this study reveal that the people of Dayeuhmanggung village have been able to realize the existence of religious differences. Public understanding of inter-religious harmony in Dayeuhmanggung Village is still categorized as not good enough due to disagreements regarding church construction. Even though in reality it will still be a proof that there is a community effort that always maintains inter-religious harmony. Informants who adhere to Islam Regarding the case of refusal to build a church in Dayeuhmanggung village themselves, they feel that the tolerance that exists on a daily basis is quite good. However, related to the construction of the church to be built at that time, according to them, it was not something that was easily accepted by local residents because the majority of the people in the village embraced Islam. The informant who is a Christian said that judging from the cases that had occurred some time ago, he felt that tolerance in the area could be paid more attention to. the absence of a church place of worship makes it difficult for them to worship easily. There is a fear based on the concerns of the majority religious group, namely Islam, over events that have occurred previously, such as cases in other areas where there are areas where the majority of Muslims continue to build churches, making other residents convert to religion, which is the reason for the refusal to be carried out by residents.